Sensitivity of rabbit fibrochondrocytes to mycoplasmas - Nascimento,Carlos Manuel de Oliveira (2002)
Primary cell culture from rabbit meniscus (fibrochondrocytes-FcrC) was infected for 24 hours with different inocula (10² to 10(7) Colony Forming Units-CFU) of Mycoplasma hominis PG-21, M. pneumoniae FH and 1428 or M. arthritidis PG-6. The severity of the different obtained cytophatic effects-CPE was inoculum, Mycoplasma species and strain dependant. These bacteria were recovered from all infected FcrC and the SP4 medium for mycoplasmas also caused toxic effect on the FcrC. It was concluded that rabbit fibrochondrocytes were sensitive to mycoplasma infection, as well as to the SP4 mycoplasma medium.